Trends and Conceptual Shifts in Organizational Culture Research in SMEs: A Bibliometric Analysis - Rini Fatmawati; Amelia Salsabila Khairunnisa (Apollo: Journal of Tourism and Business, 2026)
This study examines the development of organizational culture research in small and medium enterprises (SMEs) through a systematic literature review and bibliometric analysis. Data were collected from the Scopus database using the PRISMA 2020 framework, resulting in 495 relevant journal articles published between 2015 and 2025. The analysis combines keyword co-occurrence, co-citation analysis, bibliographic coupling, and thematic evolution overlay using VOSviewer to map both the intellectual foundations and the current research front of the field. The findings reveal a significant increase in research output, particularly after 2022, with strong contributions from Southeast Asia. Organizational culture emerges as a central construct linked to multiple thematic areas, including digital transformation, leadership, performance management, employee behavior, and safety culture. Three-period thematic evolution evidence directly supports a conceptual shift in which organizational culture has moved from a static, trait-based construct toward a dynamic, capability-based mechanism that supports SMEs' adaptation to digitalization and sustainability challenges. Theoretically, the study contributes by (i) repositioning SME organizational culture within the Dynamic Capabilities View, (ii) integrating five thematic clusters into a multi-level framework, and (iii) proposing a context-sensitive research agenda for resource-constrained, owner-managed firms. These findings provide a comprehensive overview of the literature and offer directions for future research and practical implications for SME development.